STUDY OF THE FIELD OF VISION DYNAMICS AGAINST THE BACKGROUND OF GLAUCOMOUS OPTICOPATHY TREATMENT BY COMBINED METHOD - V. E. PISKUN; A. S. VYDROV (Кубанский научный медицинский вестник)
Aim. To study the dynamics of changes in the field of vision against the background of the treatment of glaucomous opticopathy in patients with the primary open-angle II "A" stabilized glaucoma stage by a combined method involving the use of intranasal nootropic "Semax 0.1%" and percutaneous neuroelectrostimulation using the ESOM apparatus. Materials and methods. One group of patients included 38 patients treated with the proposed method, the second group included 29 patients receiving trophic treatment. The field of vision was studied using the automatic static perimeter "Perigraph Perikom"; the data were expressed in terms of sum of degrees of computer perimetry for 8 meridians. Results. Assessment of indicators was made after the end of the course of treatment, after 1, 3 and 6 months. The improvement of the studied indicator in the first group immediately after the course of treatment was observed at 9.65%, the result remained significantly higher throughout the study period, in the 2nd group the index increased by 4.5% and after 6 months was back to the initial value. Conclusion. The combined method of treatment of glaucomous opticopathy in patients with POAG II A of the stabilized stage allows toachieve an improvement in the sum of degrees of computer perimetry for a period of up to six months. High efficiency was noted in comparison with traditional therapy.